1966
DOI: 10.1002/aja.1001190105
|View full text |Cite
|
Sign up to set email alerts
|

The effect of relaxin on the endometrium of monkeys histological and histochemical studies

Abstract: Castrated or juvenile monkeys were given estrogen, progesterone and relaxin in various doses and combinations. Relaxin induced: (1) a dilatation of the superficial endometrial blood vessels and proliferation of their endothelial cells; this effect may be regarded as due to relaxin alone; (2) an intensified differentiation of the endometrial stroma cells into predecidual cells and granulocytes, dependent on estrogen priming and the simultaneous injection of progesterone; (3) a periarteriolar mantle-like accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1968
1968
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…The results of these earlier studies, also in the rhesus monkey, suggested that relaxin induces proliferation of endothelial cells of endometrial blood vessels and dilatation of superficial endometrial blood vessels (33). Animals in which administration of relaxin-containing extracts was discontinued but steroid treatment was maintained showed reduced endothelial proliferation and dilatation (32). Thus, relaxin seemed necessary to maintain endothelial proliferation and vascular dilatation in the endometrium of the rhesus monkey.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The results of these earlier studies, also in the rhesus monkey, suggested that relaxin induces proliferation of endothelial cells of endometrial blood vessels and dilatation of superficial endometrial blood vessels (33). Animals in which administration of relaxin-containing extracts was discontinued but steroid treatment was maintained showed reduced endothelial proliferation and dilatation (32). Thus, relaxin seemed necessary to maintain endothelial proliferation and vascular dilatation in the endometrium of the rhesus monkey.…”
Section: Discussionmentioning
confidence: 73%
“…Uterine weight, P ϭ 0.014. bition of MMP expression, allowing maintenance of connective tissue integrity, provides evidence for relaxin's important role in endometrial support. Hisaw and coworkers (32,33) performed the first studies to suggest that relaxin affects endometrial vascularization. The results of these earlier studies, also in the rhesus monkey, suggested that relaxin induces proliferation of endothelial cells of endometrial blood vessels and dilatation of superficial endometrial blood vessels (33).…”
Section: Discussionmentioning
confidence: 99%
“…The first evidence suggesting that RLX affects the vasculature was based on histological studies conducted in the uterus. In 1966, Dallenbach-Hellweg and colleagues (18) described an enlargement of arterioles and capillaries in the superficial portions of the endometrium of castrated monkeys treated with RLX (18). In a later study also in monkeys, they reported not only an enlargement of the vessels but also endothelial cell proliferation in the endometrial vessels (48).…”
Section: Influence Of Rlx On the Vasculature Of Other Organsmentioning
confidence: 89%
“…Uterotrophic actions of relaxin, first described in the rat (Steinetz et al 1957), include both uterine water imbibition (Steinetz et al 1957, Zarrow & Brennan 1957 and increased uterine dry matter content associated with protein, collagen and glycogen accretion (Steinetz et al 1957, Vasilenko et al 1980, 1981, Vasilenko & Mead 1987. Early studies indicating that relaxin-rich extracts promoted endometrial growth in juvenile and ovariectomized rhesus monkeys (Hisaw & Hisaw 1964, Dallenbach-Hellweg & Hisaw 1966 were later confirmed by work involving the purified hormone (Goldsmith et al 2004), which showed that relaxin also stimulated endometrial angiogenesis. Consistently, relaxin administered in the peri-implantation period increased endometrial thickness in the macaque (Hayes et al 2004).…”
Section: Introductionmentioning
confidence: 99%